Preparation And Characterization Of Citric Acid Cross-Linked Carboxymethylcellulose Hydrogel - Tan, Kai Qi (Universiti Sains Malaysia, 2021)
Hydrogel is a network of water-containing flexible polymer chains physically or chemically cross-linked in three-dimensional form. Citric acid cross-linked carboxymethyl cellulose (CMC) hydrogels have attracted attention for their biodegradability, high mechanical stability, and good water-absorbing ability. In this study, citric acid cross-linked CMC hydrogel was prepared using different preparation methods to enhance its physical and mechanical properties. The citric acid cross-linked CMC hydrogel was prepared by varying the concentration of CMC at 2, 3, and 4 w/v % and varying the concentration of citric acid at 10, 15, and 20 mol/mol %. The stirring condition of hydrogel was varied at room temperature and heating (50 - 55 °C); while the drying condition of hydrogel was varied at fridge-dried (4 °C) and oven-dried (60 °C). The SEM and BET analysis revealed that the hydrogel is non-porous and water absorption occurred via hydrogen bonding between water and CMC molecules. It is proven that a higher concentration of CMC and citric acid increased the cross-linking density. High cross-linking density significantly decreased the swelling ratio and degradation ratio. The hydrogel composition of 4 w/v % CMC 20 m/m % citric acid prepared by stirring at a heating condition and oven-dried was the most stable hydrogel with a swelling ratio of 1879.89 % and a low degradation ratio of 12.07 %.